Impact of processing prior to thermomechanical extrusion of starchy materials - Lopez, Linda (2003)
Dry pet foods are composed of cereal, proteins, fats, fibres and other minor components. The manufacturing process comprises a first step where the dry ingredients are ground to a suitable particle size and blended, a second step where the dry powder is mixed with water and steam in a preconditioner and then extruded and a final step where the product is dried and coated. The aim of this work was to study the effects of the unit operations prior to thermos mechanical extrusion in the dry pet food process. The study focuses especially on the structure of the final product therefore, after studying a typical pet food recipe, a model system using cereal only or cereals and fats was considered. The grinding process was shown to impact on the physicochemical characteristics of a pet food premix by affecting the degree of starch damage, the water absorption and water solubility properties or the total charge of the mix. The grinding method was also found to be critical as grinding ingredients together and multiple pass grinding produced more starch damage. The resulting premixes from different grinding methods were affecting the extrusion process and the extrudates characteristics. Extruded mixes with the lowest starch damage, obtained by single pass grinding presented higher expansion than mixes produced by two pass grinding. Few studies have reported the effect of preconditioning on extrusion, therefore, a model preconditioning apparatus was first built to analyse the effect of residence time and initial moisture on maize grits physicochemical characteristics. The results of this study showed that limited precooking occurs at the preconditioner stage (0 to 80% loss in crystallinity). This precooking reduces water self diffusion coefficient in the particle, as measured by pulse field gradient NMR, decreases powder bulk density and increases powder compressibility. At the highest moisture contents (33% wb) and the highest residence time (240s), maize grits can lose its hydrated powder state and form a viscous paste. The different particle sizes used (from 240 to 476 µm modal diameter) did not show different behaviours. The effect of preconditioning on extrusion was also studied using the model preconditioner. Results showed that prehydration and pre-heating increased homogeneity of the material entering the extruder and reduced the specific mechanical energy (SME). This increased in homogeneity allows a more homogeneous starch conversion in the extruder as no remnant native starch granule was found in the preconditioned sample for 240s. The results from the model system were then partially confirmed using a pilot plant double-shafted Buhler preconditioner on maize grits of various particle size (330 to 1365 µm modal diameter). The results showed that preconditioning decreases SME but also allows a higher expansion. The SME was negatively correlated with the temperature of the mix immediately after preconditioning (at the extruder inlet) and the compressibility of the preconditioned material. The crystallinity of starch in the end product (Vh or Eh and Vh) was also dependant on the preconditioning treatment. Pre-heating reduced the Eh pattern of the extrudates. Finally, the interactions between fats and starch during extrusion have also been studied. It has been shown that the levels of free fatty acids in fats commonly used in the dry pet food industry (sunflower oil, beef tallow and poultry fat) can affect markedly the expansion, foam structure and pasting characteristics of extrudates. This was especially correlated to the formation of crystalline complexes between amylose and free fatty acids.